2015
DOI: 10.1152/ajpheart.00776.2014
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor modulates angiotensin signaling in the hypothalamus to increase blood pressure in rats

Abstract: Brain-derived neurotrophic factor (BDNF) expression increases in the paraventricular nucleus of the hypothalamus (PVN) in response to hypertensive stimuli including stress and hyperosmolarity. However, it is unclear whether BDNF in the PVN contributes to increases in blood pressure (BP). We tested the hypothesis that increased BDNF levels within the PVN would elevate baseline BP and heart rate (HR) and cardiovascular stress responses by altering central angiotensin signaling. BP was recorded using radiotelemet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 59 publications
10
34
0
Order By: Relevance
“…On the contrary, Met allele was either linked to thin phenotype in British females, Chinese Han adolescents and Korean smokers [3032] or lacked of relationship with obesity in German extremely obese children and adolescents and underweight students [33]. The inconsistency of these results indicates the uncertain association between BDNF Val66Met and obese phenotype which might be modulated by other factors such as ethnic background, age, gender, living environment, dietary structure and lifestyle [34]. Intriguingly, the Met allele carriers in OG exhibited a lower BMI level, implying that the descendants of nonagenarians may endow other unraveled buffering genotypes which may attenuate the unfavorable effect of this variant.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Met allele was either linked to thin phenotype in British females, Chinese Han adolescents and Korean smokers [3032] or lacked of relationship with obesity in German extremely obese children and adolescents and underweight students [33]. The inconsistency of these results indicates the uncertain association between BDNF Val66Met and obese phenotype which might be modulated by other factors such as ethnic background, age, gender, living environment, dietary structure and lifestyle [34]. Intriguingly, the Met allele carriers in OG exhibited a lower BMI level, implying that the descendants of nonagenarians may endow other unraveled buffering genotypes which may attenuate the unfavorable effect of this variant.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic factors not only contribute to synaptic connectivity but also mediate changes in neuronal excitability (Benarroch, 2015; Blum et al, 2005; Cao et al, 2010; Rose et al, 2004). To this end, recent studies have investigated the contribution of the ubiquitous neurotrophin brain-derived neurotrophic factor (BDNF) toward promoting autonomic imbalance during RAS activation (Becker et al, 2016; Becker et al, 2015; Clayton et al, 2014; Erdos et al, 2015a; Schaich et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…36 A new study has shown a connection between RAS and BDNF, where BDNF modulates angiotensin signaling. 37 At the same time, there are studies suggesting the neuro-protective actions of RAS blockers involving BDNF. 38,39 Considering all together, there are no clinical studies that have explored the direct relationship between RAS and BDNF.…”
Section: Discussionmentioning
confidence: 99%